CXCR4 pharmacogical inhibition reduces bone and soft tissue metastatic burden by affecting tumor growth and tumorigenic potential in prostate cancer preclinical models. Issue 12 (12th June 2015) - Gravina, Giovanni Luca; Mancini, Andrea; Muzi, Paola; Ventura, Luca; Biordi, Leda; Ricevuto, Enrico; Pompili, Simona; Mattei, Claudia; Di Cesare, Ernesto; Jannini, Emmanuele A.; Festuccia, Claudio
<x xml:space="preserve">Abstract</x> BACKGROUND The majority of prostate cancer (Pca) patient morbidity can be attributed to bone metastatic events, which poses a significant clinical obstacle. Therefore, a better understanding of this phenomenon is imperative and might help to develop novel therapeutic strategies. Stromal cell‐derived factor 1α (SDF‐1α) and its receptor CXCR4 have been implicated as regulators of bone resorption and bone metastatic development, suggesting that agents able to suppress this signaling pathway may be used as pharmacological treatments. In this study we studied if two CXCR4 receptor antagonists, Plerixafor and CTE9908, may affect bone metastatic disease induced by Pca in preclinical experimental models METHODS To verify the hypothesis that CXCR4 inhibition affects Pca metastatic disease, selective CXCR4 compounds, Plerixafor, and CTE9908, were tested in preclinical models known to generate bone lesions. Additionally, the expression levels of CXCR4 and SDF‐1α were analyzed in a number of human tissues derived from primary tumors, lymph‐nodes and osseous metastases of Pca as well as in a wide panel of human Pca cell lines to non‐tumorigenic and tumorigenic phenotype. RESULTS Bone‐derived Pca cells express higher CXCR4 levels than other Pca cell lines. This differential expression was also observed in human Pca samples. In vitro evidence supports the hypothesis that factors produced by bone microenvironment differentially sustain CXCR4 and SDF1‐α expression with respect to prostate microenvironment determining increased efficacy toward Plerixafor. The use of SDF1‐α neutralizing antibodies greatly reduced the increase of CXCR4 expression in cells co‐cultured with bone stromal cells (BMSc) and to a lesser extent in cells co‐cultured with prostate stromal cells (HPSc) and partially reduced SDF1‐α Plerixafor efficacy. SDF‐1α induced tumor cell migration and invasion, as well as MMP‐9, MMP‐2, and uPA expression, which were reduced by Plerixafor. The incidence of X‐ray detectable bone lesions was significantly reduced following Plerixafor and CTE9908 treatment Kaplan–Meier probability plots showed a significant improvement in the overall survival of mice treated with Plerixafor and CTE9908. The reduced intra‐osseous growth of PC3 and PCb2 tumor cells after intratibial injection, as a result of Plerixafor and CTE9908 treatment, correlated with decreased osteolysis and serum levels of both mTRAP and type I collagen fragments (CTX), which were significantly lower with respect to controls. CONCLUSIONS Our report provides novel information on the potential activity of CXCR4 inhibitors on the formation and progression of Pca bone and soft tissue metastases and supports a biological rationale for the use of these inhibitors in men at high risk to develop clinically evident bone lesions. Prostate 75:1227–1246, 2015. © 2015 Wiley Periodicals, Inc.